HUKUM PENGANGKATAN ANAK DI NEGARA MUSLIM: KAJIAN KOMPARATIF ATAS ASPEK LEGAL-FORMAL DAN IMPLIKASI YURIDIS - Ahmad In'am Awaluddin; Rifky Nurhimawan (SAMAWA, 2025)
This paper aims to provide a comprehensive explanation of the regulations on child adoption in various Muslim countries, focusing on the legality, legal status of children, and legal implications. The research method used is library research. The data obtained in this study are from several journals, articles, and other literature related to the discussion of the law of child adoption in Muslim countries. This study uses a comparative approach by comparing the legal system of child adoption in various Muslim countries, either from the formal legal aspect or from the legal implications. The results of this study show that each Muslim country has its own legal rules in terms of child adoption. Legally, adoption in Muslim countries allows the adoption of children which aims to provide welfare to the child's life, but the terminology used is different, thus giving rise to different perceptions in terms of child adoption arrangements. The diversity of regulations in the context of child adoption in various Muslim countries not only reflects differences in legal interpretations, but also manifests socio-cultural dynamics and the evolution of Islamic legal thought in different regions. The influence of classical jurisprudence remains a strong foundation in policy formulation in the majority of Muslim countries, but legal adaptations and innovations continue to evolve to respond to the needs of contemporary society Kata Kunci: Legality of Law, Adoption, Muslim Countries